Mechanistic Insights into Glycerol Oxidation to High-Value Chemicals via Metal-Based Catalysts - Junqing Li; Ying Tu; Kelin He; Chao Chen; Lixing Liang; Chongze Ruan; Qitao Zhang (Molecules)
The oxidation of glycerol offers a valuable route for producing high-value chemicals. This review provides an in-depth analysis of the current advancements and mechanistic insights into novel metal-based catalysts for glycerol oxidation. We discuss the catalytic roles of both precious metals (e.g., Pt, Pd, Au), noted for their high efficiency and selectivity, and cost-effective alternatives, such as Ni, Cu, and Fe. Bimetallic and metal oxide catalysts are highlighted, emphasizing synergistic effects that enhance catalytic performance. This review elucidates the key mechanism involving selective adsorption and oxidation, providing detailed insights from advanced spectroscopic and computational studies into the activation of glycerol and stabilization of key intermediates, including glyceraldehyde and dihydroxyacetone. Additionally, selective carbon–carbon bond cleavage to yield smaller, valuable molecules is addressed. Finally, we outline future research directions, emphasizing the development of innovative catalysts, deeper mechanistic understanding, and sustainable process scale-up, ultimately advancing efficient, selective, and environmentally friendly catalytic systems for glycerol valorization.